2001
DOI: 10.1002/ijc.1551
|View full text |Cite
|
Sign up to set email alerts
|

Superantigen enhanced protection against a weak tumor-specific melanoma antigen: Implications for prophylactic vaccination against cancer

Abstract: B16F10 melanoma is a tumor derived from C57BL/6 mice that has been found to be poorly immunogenic and highly aggressive. Here we have shown that vaccination of mice with irradiated B16F10 cells followed by treatment with a combination of staphylococcal enterotoxins A and B (SEA/ SEB) leads to significant and specific protection against subsequent challenge with viable B16F10 cells (at least 25-fold greater than a lethal dose). Also, 75% of mice surviving over 150 days remained tumor-free after rechallenge with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…For example, IFN-g and IFN-a were shown to inhibit the proliferation of PC3 and DU145 prostate cancer cell lines (van Moorselaar et al, 1991). In addition, previous studies have indicated that IFNs are capable of modulating the expression of various suppressor genes and oncogenes (Hobeika et al, 1998;Kominsky et al, 2000).…”
mentioning
confidence: 99%
“…For example, IFN-g and IFN-a were shown to inhibit the proliferation of PC3 and DU145 prostate cancer cell lines (van Moorselaar et al, 1991). In addition, previous studies have indicated that IFNs are capable of modulating the expression of various suppressor genes and oncogenes (Hobeika et al, 1998;Kominsky et al, 2000).…”
mentioning
confidence: 99%
“…Importantly, ErbB-2 is frequently overexpressed in carcinomas, particularly mammary and ovarian carcinomas, and is associated with a poor prognosis (8 -10). ErbB-2 antibodies (11,12) and agents such as interferon (13) or tyrosine kinase inhibitors (14) decrease the growth of ErbB-2-expressing tumor cells and also reduce the cellular level of ErbB-2 (15). In many of these instances the decreased growth provoked by the loss of ErbB-2 is due to increased apoptosis.…”
mentioning
confidence: 99%
“…IFN treatment of prostate cancer cells is known to inhibit cell proliferation (Sica et al, 1994;Kominsky et al, 2000). However, it is not known whether IFNtreatment of PrSCs results in inhibition of cell growth.…”
Section: Regulation Of Androgen Receptor Levels By Interferons Z Basrmentioning
confidence: 99%
“…Both types of IFNs function through transcriptional activation of IFNactivatable genes encoding the IFN-inducible proteins that mediate the biological activities of IFNs. Importantly, treatment of human prostate cancer cell lines with the type I IFN (Sica et al, 1994) or the type II IFN (Kominsky et al, 2000) is known to inhibit cell growth. Additionally, treatment of human prostate cancer cell line PC-3 with natural IFN-beta is known to upregulate the AR protein levels (Sica et al, 1994).…”
mentioning
confidence: 99%